(untitled) (Semiárida, 2020)
Results from 5 experiments with Coelorachis selloana, a native species of the northeast region of Uruguay are reported; different ecological factors were assessed in paddocks and in the glasshouse. The species was found mainly on clay soils and responded linearly to nitrogen applications up to 100 units; water stress significantly reduced total dry matter production compared with an irrigated control; intensively and frequently cut plants (cut every 2 weeks at 2cm) yielded significantly less dry matter per plant as compared with alleviated ones (cut every 8 weeks); under field conditions its presence increased significantly in conditions with high forage allowance as compared with low forage allowance during the growing season.